Pesona Kreativitas Anak-Anak PAUD SPS NUSA INDAH BUKIR dalam Pameran Lukisan dari Serbuk Kayu - M. Mascun Andianto; Dewi Nurmalitasari; Dian Rahmawati; Dwi Aprilia Damayanti; Aswin Saka (Lembaga Pengembangan Kinerja Dosen, 2024)
Early Childhood Education (PAUD) is very important for the intellectual, emotional, social, and physical development of children. PAUD SPS NUSA INDAH BUKIR in collaboration with KKN students from Bukir Village, Universitas PGRI Wiranegara Pasuruan held an art exhibition using sawdust to encourage children's creativity. Painting technique training and exhibition of works were included in the preparation, implementation, and evaluation process of the event. The results of the exhibition showed that sawdust helped children become creative and improved their fine motor skills, imagination, and social skills. Children felt more confident after receiving gifts. The involvement of KKN students in the exhibition showed the synergy between education and community service, which had a positive and sustainable impact. It is hoped that this exhibition will serve as a model for activities in PAUD that combine art, creativity, and environmental awareness.